Human papillomavirus prevalence in a Mid‐European oral squamous cell cancer population: A cohort study. (8th June 2018) - Dalla Torre, Daniel; Burtscher, Doris; Soelder, Elisabeth; Offermanns, Vincent; Rasse, Michael; Puelacher, Wolfgang
Abstract: Objectives: Human papillomavirus infection has been investigated intensively regarding oropharyngeal carcinoma. However, there is still lack of knowledge about the impact of oral HPV infections concerning oral squamous cell carcinoma. This study investigates the prevalence of oral HPV infection in such patients, identifying possible differences between HPV+ and HPV– patients. Subjects and Methods: One hundred and six consequent patients were investigated. After completion of a study questionnaire regarding risk factors, a brush smear sample was taken in each subject to identify the individual oral HPV status (overall/low risk/high risk). Results: About 35.8% of the patients were tested positive for HPV in the oral cavity (14% low risk, 28.3% high risk). Patients with oral HPV infection and high‐risk HPV infection were significantly younger ( p  < 0.001) and had a higher alcohol consumption ( p  = 0.0075 resp. p  = 0.0022). A high number of different sexual partners were significantly correlated with any type of HPV infection. At last, patients with high‐risk oral HPV infection had experienced more tooth extractions during their lifetime. Conclusion: Oral HPV infections may influence the course of disease of oral squamous cell carcinoma as HPV+ patients are about 10 years younger. It seems that high alcohol consumption facilitates high‐risk HPV infection. It may be presumed that both alcohol consumption and high‐risk oral HPV infection act synergistically, explaining earlier cancer onset.